Insurance Search and Switching Behavior - Jonneke Bolhaar; Bas van der Klaauw; Maarten Lindeboom (Tinbergen Institute, 2010)
This paper looks into the search behavior of consumers in the market for health insurance contracts. We consider the recent health insurance reform in The Netherlands, where a private-public mix of insurance provision was replaced by a system based on managed competition. Although all insurers offer the same basic package (determined by the government), there is substantial premium dispersion. We develop a simple consumer search model containing the main features of the Dutch health insurance system. This model provides us with a number of hypotheses, which we test using data from the Dutch Health Care Consumer Panel. The data confirm the standard predictions on consumer choice (i.e. there is adverse selection and a lower premium increases coverage). We also find that consumers with lower search costs are more likely to receive a group contract offer. This generates a situation of price discrimination where individuals without group contracts and higher s! earch costs pay higher premiums and buy lower insurance coverage.
Keywords: I11; D83; 330; health insurance; consumer search behavior; Dutch health insurance reform; Krankenversicherung; Konsumentenverhalten; Gesundheitsreform; Niederlande